Yellowish flecks in Leber's congenital amaurosis. Issue 10 (October 1984) - Chew, E.; Deutman, A.; Pinckers, A.; Aan de Kerk, A.
Abstract : The fundus abnormalities of Leber's congenital amaurosis are extremely variable, from normal to salt-and-pepper changes to typical retinitis pigmentosa. A less commonly seen appearance is that of multiple, irregular shaped, yellowish white flecks deep in the midperipheral retina in a periarteriolar distribution. The nasal fundus as well as the posterior pole are spared. Such a case is presented along with a four-year follow-up together with the fluorescein angiographic findings. The flecks appear to be specific for this entity.